2016
DOI: 10.3389/fmicb.2016.01476
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptomic Analysis Reveals Novel Insights into the Adaptive Response of Skeletonema costatum to Changing Ambient Phosphorus

Abstract: Phosphorus (P) is a limiting macronutrient for diatom growth and productivity in the ocean. Much effort has been devoted to the physiological response of marine diatoms to ambient P change, however, the whole-genome molecular mechanisms are poorly understood. Here, we utilized RNA-Seq to compare the global gene expression patterns of a marine diatom Skeletonema costatum grown in inorganic P-replete, P-deficient, and inorganic- and organic-P resupplied conditions. In total 34,942 unique genes were assembled and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 108 publications
5
30
0
Order By: Relevance
“…Consistent with this, in the sequenced metatranscriptome, several sets of H. akashiwo genes associated with P metabolism were up‐regulated in the bloom samples. First, we observed up‐regulated expression of inorganic phosphate transporter, pho4 and spts , genes that have been shown to facilitate efficient uptake of P under P‐limited conditions (Dyhrman et al ., ; Wurch et al ., ; Zhang et al ., ; Haley et al ., ). Second, utilization of DOP via AP to sustain growth has been documented in many phytoplankton species (Dyhrman et al ., ; Lin et al ., ).…”
Section: Discussionmentioning
confidence: 98%
“…Consistent with this, in the sequenced metatranscriptome, several sets of H. akashiwo genes associated with P metabolism were up‐regulated in the bloom samples. First, we observed up‐regulated expression of inorganic phosphate transporter, pho4 and spts , genes that have been shown to facilitate efficient uptake of P under P‐limited conditions (Dyhrman et al ., ; Wurch et al ., ; Zhang et al ., ; Haley et al ., ). Second, utilization of DOP via AP to sustain growth has been documented in many phytoplankton species (Dyhrman et al ., ; Lin et al ., ).…”
Section: Discussionmentioning
confidence: 98%
“…P. tricornutum and T. pseudonana were chosen as the localization of the different isozymes are well predicted for these species [37,38]. The treatment was also similar in the three compared experiments ( P. tricornutum and S. costatum , 96 h P depletion [28,31]; T. pseudonana , 100 h P depletion [26]). Expression data were only available for a few carbon metabolism pathways for S. costatum .…”
Section: Carbon Metabolism Responses To Phosphorus Limitation In Diatomsmentioning
confidence: 99%
“…Polyphosphate serves as both a major cellular phosphate reservoir and an energy storage pool that can be used as a source of ATP (65). Some phytoplankton species can acquire Pi to synthesize polyphosphate under Pi-sufficient conditions and degrade polyphosphate to release Pi through upregulation of VTC4 under Pi-deficient conditions (66,67). These results indicated that H. akashiwo initiates external phosphate transport and internal storage systems to adapt to low-Pi environments, thus supporting its bloom prior to that of P. donghaiense.…”
Section: Discussionmentioning
confidence: 99%
“…Protein phosphatase, acid phosphatase, and 3=(2=),5=-bisphosphate nucleotidase hydrolyze phosphoric esters, while phospholipase and phosphatidylinositol phospholipase C hydrolyze structural phospholipids to release phosphate (69)(70)(71). These enzymes and their homologs involved in DOP reutilization are found to be highly expressed under P-deficient conditions (66)(67)(68). The multiple but varied DOP utilization strategies enable H. akashiwo and P. donghaiense to adapt to low-Pi concentrations during their blooming periods.…”
Section: Discussionmentioning
confidence: 99%